Pengembangan Sistem Presensi Dosen Berbasis Geolocation Untuk Meningkatkan Akurasi Dan Efisiensi Pencatatan Kehadiran Perkuliahan - Dani Yusuf; Siti Setiawati (Journal of Informatic and Information Security, 2024)
This study aims to develop and implement a faculty attendance system based on geolocation, utilizing GPS technology for automatic recording of faculty attendance. This system is expected to enhance efficiency, accuracy, and transparency in the attendance process, as well as facilitate the management of faculty attendance data by administrators. The method used in this research is the prototype development method, which allows for iterative system development based on user feedback. The system development process includes needs identification, prototype design, development of the geolocation-based attendance application, system testing, as well as revisions and improvements to the prototype. The results of initial testing indicate that this attendance system successfully records faculty attendance time and location accurately using GPS technology, while also enabling administrators to monitor attendance reports in real-time. This research is expected to contribute to the utilization of geolocation technology to improve academic administration efficiency and provide practical solutions in managing faculty attendance in higher education institutions.